Rock formation characterization for carbon dioxide geosequestration: 3D seismic amplitude and coherency anomalies, and seismic petrophysical facies classification, Wellington and Anson-Bates fields, Sumner County, Kansas, USA - Ohl, Derek Robert (Kansas State University, 2012)
Amid increasing interest in geological sequestration of carbon dioxide (CO2), detailed rock formation characterization has emerged as priority to ensure successful sequestration. Utilizing recent advances in the field of 3D seismic attributes analysis, offers improved opportunities to provide more details when characterizing reservoir formations. In this study, several post-stack seismic attributes integrated with seismic modeling for highlighting critical structural elements and petrophysical facies variation of rock formations at Wellington and Anson-Bates fields, Sumner County, Kansas. A newly acquired 3D Seismic data set and several geophysical well logs are also used to achieve the objectives of this study. Results sought in this study are potentially important for understanding pathways for CO2 to migrate along. Seismic amplitude, coherency, and most negative curvature attributes were used to characterize the subsurface for structural effects on the rock formations of interest. These attributes detect multiple anomaly features that can be interpreted as small throw faults. However, in this study, there is a larger anomalous feature associated with the Mississippian formation that can be interpreted as a small throw fault or incised channel sand. Determining which of the two is very important for flow simulation models to be more exact. Modeling of the seismic was undertaken to help in the interpretation of the Mississippian amplitude anomaly. An artificial neural network, based on well log porosity cross-plots and three seismic attributes, was trained and implemented to yield a seismic petrophysical facies map. The neural network was trained using three volume seismic waveform attributes along with three wells with difference in well log porosity. A reworked lithofacies along small throw faults has been revealed based on comparing the seismic structural attributes and the seismic petrophysical facies. Arbuckle formation characterization was successful to a certain degree. Structural attributes showed multiple faults in the northern half of the survey. These faults are in agreement with known structure in the area associated with the Nemaha uplift. Further characterization of the Arbuckle was hindered by the lack of well data. This study emphasizes the need for greater attention to small-scale features when embarking upon characterization of a reservoir for CO2 based geosequestration.
Keywords: Carbon Dioxide Sequestration; Coherency; Seismic Attributes; Rock Formation Characterization; Geosequestration; Petrophysical Facies Modeling; Geology (0372); Geophysics (0373)